IMPLEMENTASI PEMELIHARAAN SARANA DAN PRASARANA PERPUSTAKAAN DI SMK NEGERI 3 TEKNOLOGI DAN REKAYASA JAYAPURA TAHUN AJARAN 2019/2020 - Ancelina Butu; Desy Anita Karolina Sembiring; Patrisya F. Yobi (Universitas Cenderawasih, 2020)
This study aimed to describe the maintenance of library, maintenance of equipment and maintenance of library equipment in SMK Negeri 3 Teknologi dan Rekayasa Jayapura. This research method was descriptive with qualitative approach. The data source was the principal, library employees, two teachers and five students. Data collection techniques were carried out with in-depth interviews, observations, and documentation studies. Data analysis used by researchers were data reduction, data collection, data presentation and conclusions. The results showed that (1) The maintenance of library space had not been carried out properly because there were still shortcomings in the implementation, namely, planning was not done. (2) Maintenance of library equipment had not been carried out properly, due to the busyness of the library officers outside the school and there were still some damaged equipment. (3) The maintenance of library equipment had been carried out quite well because the school got assistance in the form of books, cleaned up equipment and some equipment in the library. The findings of this research could be used as a reference to produce a procedure for maintaining good library facilities and infrastructure in schools.Keywords: Maintenance of library space; Library equipment; Library equipment